2020
DOI: 10.29392/001c.12252
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and recommendation of oral rehydration solution and zinc for management of childhood diarrhoea among patent and proprietary medicine vendors in Port Harcourt, Nigeria

Abstract: Background In Nigeria, where patent and proprietary medicine vendors (PPMVs) provide care in 55% of common paediatric illnesses, child deaths from diarrhoeal diseases stands at 104000; 14% of total all-cause child mortality. Our aim was to investigate PPMVs knowledge of presentation, cause, treatment and prevention of childhood diarrhoea, and their recommendation of oral rehydration solution (ORS) and zinc in the treatment of sick children in Port Harcourt, Nigeria. Methods A cross-sectional design, structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
2
1
Order By: Relevance
“…This finding is similar with studies in Nigeria [24] and Ethiopia [22]. The plausible possible reason might be those mothers with higher education level usually have an increased awareness and knowledge about the importance of zinc for the management of childhood diarrheal diseases compared to non-educated once [29,33].…”
Section: Plos Onesupporting
confidence: 89%
“…This finding is similar with studies in Nigeria [24] and Ethiopia [22]. The plausible possible reason might be those mothers with higher education level usually have an increased awareness and knowledge about the importance of zinc for the management of childhood diarrheal diseases compared to non-educated once [29,33].…”
Section: Plos Onesupporting
confidence: 89%
“…Another study conducted in Philippines revealed that a low proportion (21%) of primary students possesses knowledge on the signi cance of ORS or zinc in the treatment of diarrhea; however, only a moderate improvement (54%) in the proportion of these students was observed after intervention [14]. One explanation for the ignorance regarding the use of ORS or zinc as treatment options for diarrhea among students in the present study may be the lack of knowledge regarding these treatments in resource-poor settings [22]. Studies conducted in resource-poor countries have demonstrated that although communities and healthcare providers in these regions are aware of ORS or zinc, the utilization rates of these treatments are low at both the community and prescriber levels [8,23,24].…”
Section: Discussioncontrasting
confidence: 56%
“…With a significant association demonstrated between knowledge and education level, an opportunity is presented for policies and interventions that emphasize education and training of PPMVs to improve their knowledge on childhood diarrhoea (and perhaps other childhood illnesses?) and to function optimally in primary care delivery in the community [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%